CAMP PROGRAM BAHASA MELAYU SEBAGAI UPAYA MEMPERTAHANKAN IDENTITAS BUDAYA ISLAM DI MA’HAD AL-IRSYAD LIL BANAT, YALA, THAILAND (MALAY LANGUAGE CAMP PROGRAM AS AN EFFORT TO MAINTAIN ISLAMIC CULTURAL IDENTITY AT MA'HAD AL-IRSYAD LIL BANAT, YALA, THAILAND) - Khalda, Nabilah; Anshari, Muhammad Redha; Sateemae, Suhaimee (JURNAL BAHASA, SASTRA, DAN PEMBELAJARANNYA (JBSP), 2024)
AbstractMalay Language Camp Program as An Effort to Maintain Islamic Cultural Identity At Ma'had Al-Irsyad Lil Banat, Yala, Thailand. This study aims to examine the improvement of Malay language skills through the Malay Language Programme Camp at Ma'had Al-Irsyad Lil Banat in order to strengthen the Islamic cultural identity of the participants. The main problem is the lack of appreciation and understanding of the Malay language among the younger generation, which makes them prefer foreign languages. Therefore, the Malay language program camp was designed to increase the participants' interest and understanding of the language through an interactive and contextual learning approach. The research method used was a qualitative approach with a phenomenological design where data was collected through interviews and participant observation. The results showed that the program significantly improved participants' Malay language skills and cultural awareness. In addition, activities involving Malay cultural traditions successfully strengthened the participants' sense of identity as Muslims. This research is expected to contribute positively to the development of similar programs in the future to preserve Islamic cultural identity.Keywords: Malay language camp, Islamic education, language teaching.AbstrakCamp Program Bahasa Melayu sebagai Upaya Mempertahankan Identitas Budaya Islam Di Ma’had Al-Irsyad Lil Banat, Yala, Thailand. Penelitian ini bertujuan untuk melihat peningkatan keterampilan berbahasa Melayu melalui camp program bahasa Melayu di Ma’had Al-Irsyad Lil Banat terhadap penguatan identitas budaya Islam di kalangan santri. Permasalahan utama yang dihadapi adalah kurangnya apresiasi dan pemahaman terhadap bahasa Melayu di kalangan generasi muda, yang membuat mereka cenderung lebih memilih bahasa asing. Oleh karena itu, camp program bahasa Melayu dirancang untuk meningkatkan minat dan pemahaman santri terhadap bahasa tersebut dengan pendekatan belajar interaktif dan kontekstual. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan desain fenomenologi, dimana data dikumpulkan melalui wawancara dan observasi partisipatif. Hasil penelitian menunjukkan bahwa program ini secara signifikan meningkatkan keterampilan berbahasa Melayu santri dan kesadaran budaya mereka. Selain itu, kegiatan yang melibatkan tradisi budaya Melayu berhasil memperkuat rasa identitas santri sebagai umat Muslim. Penelitian ini diharapkan dapat memberikan kontribusi positif bagi pengembangan program serupa di masa depan dalam rangka pelestarian identitas budaya Islam.Kata-kata kunci: Camp Bahasa Melayu, Pendidikan Islam, Pengajaran Bahasa.